Effects of Aluminium Sulphates on Weight and Structure of Adrenal Gland of Adult Wistar Rats - Abodunrin V. K; Fakunle P. B; Saka O. S; Abijo A. Z3; Akinboro A. D; Ige M. S (International Journal of Human Anatomy, 2020)
This study evaluated the effects of aluminum sulphate exposure on the histology of adrenal gland of Wistar rats. Thirty adult Wistar rats were used for this study. The Wister rats were divided into three groups; group A was the control animals and tagged C, group B animals received 10g of alum dissolved in 1000cm3 of distilled water and were tagged T1, group C animals received 50g of alum dissolved in 1000cm3of distilled water and were tagged T2, via drinking water for duration of four weeks. Twenty-four hours after the last administration, the rats were sacrificed by cervical dislocation. The adrenal gland was excised and preserved in 10 % formosaline after which it was routinely processed for hematoxylin and eosin staining (H&E). Histological observations showed normal cell distribution in the control group but treated group revealed evidences of cellular obliteration& hemorrhagic necrosis. The results obtained from this study suggest that aluminum sulphate has a damaging effect on the structure of the adrenal gland.
Keywords: Adrenal gland